Pluripotency state transition of embryonic stem cells requires the turnover of histone chaperone FACT on chromatin - Hang Zhao; Di Li; Xue Xiao; Cuifang Liu; Guifang Chen; Xiaoyu Su; Zhenxin Yan; Shijia Gu; Yizhou Wang; Guohong Li; Jianxun Feng; Wei Li; et al. (iScience, 2024)
Summary: The differentiation of embryonic stem cells (ESCs) begins with the transition from the naive to the primed state. The formative state was recently established as a critical intermediate between the two states. Here, we demonstrate the role of the histone chaperone FACT in regulating the naive-to-formative transition. We found that the Q265K mutation in the FACT subunit SSRP1 increased the binding of FACT to histone H3-H4, impaired nucleosome disassembly in vitro, and reduced the turnover of FACT on chromatin in vivo. Strikingly, mouse ESCs harboring this mutation showed elevated naive-to-formative transition. Mechanistically, the SSRP1-Q265K mutation enriched FACT at the enhancers of formative-specific genes to increase targeted gene expression. Together, these findings suggest that the turnover of FACT on chromatin is crucial for regulating the enhancers of formative-specific genes, thereby mediating the naive-to-formative transition. This study highlights the significance of FACT in fine-tuning cell fate transition during early development.